Opportunities and Challenges in Digitalising Marine Logistics in Indonesia - Aung Ye Kyew (Collaborate Engineering Daily Book Series, 2024)
As the largest archipelagic country in the world, Indonesia has great potential in the maritime logistics industry. However, digitalization in this sector still faces challenges such as inadequate information technology infrastructure and a lack of skilled human resources in the digital field. On the other hand, the digitalization of maritime logistics offers opportunities to increase the efficiency, transparency, and traceability of supply chains, as well as reduce operational costs and the risk of goods damage. Collaboration between government, industry, and academia is key in facing challenges and exploiting digitalization opportunities. By overcoming challenges and taking advantage of digitalization opportunities, Indonesia can strengthen its position as an important maritime country and encourage national economic growth through a more efficient and modern maritime logistics industry.